A team mental model approach to understanding team effectiveness in an emergency department: A qualitative study. Issue 1 (January 2022) - Wise, Sarah; Duffield, Christine; Fry, Margaret; Roche, Michael
Objectives: To demonstrate how the team mental model concept can broaden our understanding of team effectiveness in health care by exploring the knowledge that underpins it, and the workplace conditions that sustain it in a metropolitan emergency department (ED) in Sydney, Australia. Methods: This study draws on accounts of 19 ED clinicians (registered nurses, doctors and nurse practitioners) of their teamwork practice and perceptions of their team's effectiveness through semi-structured interviews. Analysis was conducted in two stages. A thematic analysis was followed by a template analysis using the a priori themes of task, team, team process and goal knowledge to specify the content of the team's mental model. Results: The content of the ED team's mental model revealed that the knowledge the team employed to coordinate their work was deeply embedded in the team's tasks and the workplace context. Team effectiveness not only relied on how well team members coordinate, but also their ability to perform their own role effectively and efficiently. Three workplace conditions were identified as enablers to individuals acquiring the knowledge needed to work effectively in the team: stability in team membership; workplace experience; and the spatial-temporal conditions of emergency work where permanent emergency doctors and nurses executed their tasks concurrently, regularly interacted and shared a common goal. Conclusions: Getting health care teams 'on the same page' is a long-standing challenge. This study suggests that solutions may lay in the organisation of health care work, creating team stability and opportunities for team members to interact that allows a team mental model to emerge.